50 x 1% = 0.5
because 1% is equal to 1/100 so 50 x 1/100 is equal to 50/100 or 1/2 which is equal to 0.5
Answer:
-720
Step-by-step explanation:
Answer:
✔️Ratio of weight to mass in simplest form: 49/5 or 49 : 5
✔️x = 110
Step-by-step explanation:
Since the ratio of weight to mass is constant, therefore we can use any pair of values from the table to find the ratio that represents the table. Let's pick the first row:
(20, 196)
Ratio of weight to mass = 196 : 20
= 196/20
= 49/5
Or 49 : 5
✔️Let's use this ratio/proportion to find x in the table
Ratio of weight to mass = 49:5
Thus:
1078/x = 49/5
Cross multiply
x*49 = 1078*5
49x = 5,390
x = 5,390/49
x = 110
Answer:
3
Step-by-step explanation:
3/3x + 1/x+4 = 10/7x
3/3x + 1/x+4 = 10/7x , x=0,x=-4
1/x + 1/x+4 = 10/7x
1/x + 1/x+4 - 10/7x = 0
7(x+4)+7x-10(x+4) / 7x*(x+4) = 0
7x+28+7x-10x-40 / 7x*(x+4) = 0
4x-12 / 7x*(x+4) = 0
4x-12=0
4x-=12
x=3,x=0,x=-4
x=3
Answer:
3(a - b)(a + b)
Step-by-step explanation:
Factorize: (2a - b)² - (a - 2b)²
- Different of Perfect a Square rule: a² - b² = (a + b)(a - b)
(2a - b)² - (a - 2b)² = [(2a - b) + (a - 2b)] × [(2a - b) - (a - 2b)]
1. Distribute and Simplify:
Distribute the (+) sign on the first bracket and simplify: [(2a - b) + (a - 2b)] → 2a - b + a - 2b → (3a - 3b)
Distribute the (-) sign on the first bracket and simplify: [(2a - b) - (a - 2b)] → 2a - b – a + 2b → (a + b)
We now have:
(3a - 3b)(a + b)
2. Factor out the Greatest Common Factor (3) from 3a - 3b:
(3a - 3b) → 3(a - b)
3. Add "(a + b)" back into your factored expression:
3(a - b)(a + b)
Hope this helps!